Reconstructing the Meaning of the Hadith ‘Most of the Inhabitants of Hell Are Women’: A Sanad-Based, Intertextual, and Contextual Analysis - Ningrum, Ulfia; Qurrah A’yuniyyah; Vida Ravida (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2025)
Abstract This study addresses the problem of misinterpretation of the hadith stating that “women constitute the majority of the inhabitants of Hell,” which has frequently been used to support negative generalizations about women. Using the library research method, this study employs a combined approach of sanad criticism, textual and linguistic analysis, intertextual comparison with relevant Qur’anic verses and other hadiths, as well as contextual interpretation based on historical conditions. The findings reveal that although the hadith is authentically transmitted through strong, continuous chains of narration, its meaning cannot be understood literally or detached from its socio-historical background. Intertextual analysis shows that the Qur’an never designates women as inherently more likely to enter Hell, and contextual evidence indicates that the Prophet delivered this statement as a situational moral warning rather than a discriminatory judgment. The study concludes that the hadith emphasizes specific immoral traits, not gender, and must be interpreted in harmony with the Qur’an’s principles of justice and ethical accountability. Keywords: Contextualization; Hadith criticism; Intertextual approach; Women in hadith.